MEKANISME KOPING PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Latipah; Kawuryan, Uji; Pratama, Kharisma (Jurnal Riset Keperawatan dan Kesehatan, 2024)
Background: Chronic kidney failure is a progressive and irreversible renal function disorder where the body fails to maintain metabolism and fluid-electrolyte balance. Hemodialysis is a therapeutic method used to remove fluids and waste products from the body. Patients undergoing hemodialysis experience various biological and psychosocial issues during therapy. These patients exhibit coping responses or reactions, necessitating coping mechanisms to guide them toward constructive behavior. Objective: This studi aimed to understand the coping mechanisms of chronic kidney failure patients undergoing hemodialysis. Method: This study was a descriptive research with a cross-sectional approach. Sampling involved 45 respondents selected through purposive sampling. Results: The research indicates that 43 respondents (95.6%) utilize adaptive coping, while 2 respondents (4.4%) use maladaptive coping. The majority were elderly, comprising 16 respondents (35.6%), males constitute 22 respondents (51.1%), 32 respondents (71.1%) have been undergoing hemodialysis for an extended period, 16 respondents (35.6%) have a middle-level education, and 34 respondents (75.6%) have an open personality. Conclusion: The majority of chronic kidney failure patients undergoing hemodialysis at RSUD Sultan Syarif Mohamad Alkadrie Pontianak exhibit adaptive coping mechanisms.